Financial regulation and bank performance - Li, Shaofang (Singapore Springer Nature Pvt, Ltd., 2021)
This book focuses on the impact on financial regulation and examines the impact of financial regulation on bank performances from different perspectives. More specifically, this study investigates how bank sector reforms and bank regulation and supervision affect the competition, stability and risk-taking behavior in banking system.